Carbon Orientation in the Diatom Phaeodactylum tricornutum: The Effects of Carbon Limitation and Photon Flux Density - Heydarizadeh, Parisa; Veidl, Brigitte; Huang, Bing; Lukomska, Ewa; Wielgosz-Collin, Gaëtane; Couzinet-Mossion, Aurélie; Bougaran, Gaël; Marchand, Justine; Schoefs, Benoît (Frontiers in Plant Science, 2019)
Diatoms adapt to changing environmental conditions in a very efficient ways. Among the mechanisms that can be activated, the reorientation of the carbon metabolism is crucial because it allows the storage of energy into energy-dense molecules, typically lipids and or carotenoids. Beside their roles in physiology, lipids and carotenoids are commercially interesting compounds. Therefore studies dealing with this topic are both relevant for basic and applied science. If the molecular mechanisms involved in the reorientation of the carbon metabolism as a response to a deficiency in nutrient such as nitrogen or phosphorus have been partially elucidated, the impact of the carbon availability on the implementation of the reorientation mechanisms remains unclear. Indeed, it is not determined if in carbon shortage or/ limitation conditions, the same type of mechanisms are triggered than when another nutrient is deficient. The first aim of this work was to get insights into the physiological, biological and molecular processes triggered by a progressive carbon starvation in the model diatom Phaeodactylum tricornutum. The second aim was to investigate the effect of the growth light intensity on the processes. The main effects were observed under LL. The results presented here demonstrate that under carbon limitation, diatom cells still reorient the carbon metabolism toward either PEP or pyruvate that serves as a hub for the production of more complex molecules. The orientation of the carbon in either of the different pathways was partially affected by the growth photon flux density because LL provided condition for the accumulation of chrysolaminarin, while ML mostly stimulated lipid synthesis. A significant increase in the amount of proteins was observed under HL.